Circulating Interleukin-22 Is a Biomarker for Newly Diagnosed Type 2 Diabetes Mellitus and Associated with Hypoglycemic Effect of Sitagliptin - Sun P; Xiao Y; Dong Y; Feng Y; Zheng H; Liao X (Diabetes, Metabolic Syndrome and Obesity)
Peiye Sun,* Yuxi Xiao,* Yuan Dong, Yixiang Feng, Hongting Zheng, Xiaoyu Liao Department of Endocrinology, Translational Research of Diabetes Key Laboratory of Chongqing Education Commission of China, the second Affiliated Hospital of Army Medical University, Chongqing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoyu Liao; Hongting Zheng, Department of Endocrinology, Translational Research of Diabetes Key Laboratory of Chongqing Education Commission of China, the second Affiliated Hospital of Army Medical University, Chongqing, 400037, People’s Republic of China, Tel +8602368774669 ; +8602368755709, Fax +8602368755707, Email liaoxiaoyu@tmmu.edu.cn; fnf7703@tmmu.edu.cnPurpose: Interleukin-22 (IL-22) has been demonstrated to be involved in the regulation of glucose metabolism, insulin resistance and inflammation response, which indicates that IL-22 might be associated with the occurrence and progression of diabetes. This study aimed to assess serum IL-22 levels in participants with type 2 diabetes mellitus (T2DM) and analyze the association between IL-22 levels and T2DM risk.Methods: Serum IL-22 concentrations of recruited healthy participants (n=48), newly diagnosed T2DM participants (n=46), and T2DM participants receiving placebo (n=7) or dipeptidyl peptidase-4 inhibitors (DPP-4i) sitagliptin monotherapy (n=7) were measured using a commercial enzyme-linked immunosorbent assay (ELISA) kit. Mice fed a high-fat diet (HFD) were administered sitagliptin and evaluated for IL-22 and intestinal inflammation-related indicators.Results: Serum IL-22 levels were higher in the T2DM group (127.16 ± 75.35) than in healthy controls (69.18 ± 32.83, p < 0.001), significantly negatively correlated with high-density lipoprotein cholesterol (HDL-C), and positively correlated with body mass index (BMI), glycosylated hemoglobin (HbA1c) and fasting plasma glucose (FPG), regardless of adjustment for sex and age. Multivariate logistic regression analysis showed that serum IL-22 levels were associated with the risk of T2DM (OR = 2.37, 95% CI = 1.27– 4.42, p = 0.007). Additionally, sitagliptin treatment decreased the levels of IL-22 in the serum and colon tissues of T2DM participants and HFD mice. Moreover, intestinal inflammation was improved, and retinoid acid-related orphan receptor γt (RORγt, a marker of Th17 cells)- positive cells in the colon of HFD mice were decreased after sitagliptin treatment, which might be related to the reduction of IL-22.Conclusion: Serum IL-22 is a significant independent risk factor for T2DM, implying that circulating IL-22 may be a predictive biomarker and therapeutic target for T2DM.Keywords: IL-22, type 2 diabetes, sitagliptin, intestinal inflammation